DEVELOPMENT OF A SUPPLEMENTARY CURRICULUM TO ENHANCE THAI MUSIC NOTATION READING SKILLS FOR MUSIC EDUCATION STUDENTS, LAMPANG RAJABHAT UNIVERSITY - Suaychalard, Adisorn (Journal of Educational Review Faculty of Education in MCU, 2026)
The objectives of this research were: 1) to develop a supplementary curriculum to enhance Thai music notation reading skills for music education students, and 2) to study the outcomes of implementing this supplementary curriculum. The target group consisted of 23 third-year music education students enrolled in the Thai Music course during the first semester of the 2025 academic year at the Faculty of Humanities and Social Sciences, Lampang Rajabhat University. The research instruments included the developed supplementary curriculum and a Thai music notation reading skills assessment. Data were analyzed using percentage, mean and standard deviation The research findings are summarized as follows: Firstly, the developed Thai Music Note Reading Enrichment Curriculum for music education students comprises seven essential components: curriculum background and significance, principles, objectives, content structure, instructional activities, media and learning resources, and measurement and evaluation. The overall suitability of the curriculum was rated at a high level, while the supporting curriculum documents were also found to be highly appropriate. Secondly, the assessment of students' Thai music note reading skills following the implementation of the curriculum revealed an overall performance at an excellent level. The average score was 3.58, representing 85.00 percent, which successfully exceeded the pre-established criteria